Do Students With Different Majors Have Different Personality Traits? Evidence From Two Chinese Agricultural Universities - Wen, Xicheng; Zhao, Yuhui; Yang, Yucheng T.; Wang, Shiwei; Cao, Xinyu (Frontiers in Psychology, 2021)
This paper explores whether a student’s choice of major leads to certain personality traits and the reasons for this phenomenon. Specifically, we look at evidence from two Chinese universities, both of which specialize in agricultural studies. Using the Sixteen Personality Factor (16PF) questionnaire and the Neuroticism Extraversion Openness Five-Factor Inventory (NEO-FFI) questionnaire, we collected data from two groups of students: those who study agriculture-related majors (ARM), and those who study non-agriculture-related majors (NARM). The surveys all showed no significant change in personality traits during students’ freshman year. However, after three years of university study, significant personality trait changes were noted between seniors in the ARM and NARM groups. Whereas ARM seniors tended to be socially shy and lower in communicative competence, NARM seniors were better at expressing themselves and communicating with others. Although a student’s choice of profession has an influence on their personality traits, it is not the only factor. The differences between ARM and NARM training models and curricula are also undoubtedly significant. Moreover, the bias against ARM in Chinese society further magnifies the differences in personality traits among students with different majors.